Pengaruh Konten Affiliate Marketing dan Customer Review Terhadap Keputusan Pembelian Tiktok Shop Dalam Perspektif Ekonomi Islam - A.Siti Patimah; Muh. Arafah; Musrini Muis (AMAL: Jurnal Ekonomi Syariah, 2025)
Abstract: This study aims to examine the influence of affiliate marketing content and customer reviews on purchasing decisions through TikTok Shop among students of the Faculty of Islamic Economics and Business (FEBI) at IAIN Bone, from an Islamic economic perspective. The primary focus is to assess the alignment of these marketing practices with Sharia principles, particularly honesty, transparency, and fairness in economic transactions. A quantitative research approach was employed, with data collected via questionnaires distributed to 100 respondents and analysed using SPSS version 27. The findings indicate that both affiliate marketing content and customer reviews have a positive and significant impact on purchasing decisions, both individually and collectively. From the standpoint of Islamic economics, the presence of truthful and transparent information in both variables plays a crucial role in building consumer trust, promoting fair transactions, and fostering ethical and blessed economic activity. Keywords: Affiliate Marketing Konten, Customer Review, Purchase Decision, SPSS Version 27.